An Overview of Current Knowledge on in vitro Babesia Cultivation for Production of Live Attenuated Vaccines for Bovine Babesiosis in Mexico - Alvarez, J. Antonio; Rojas, Carmen; Figueroa, Julio V. (Frontiers in Veterinary Science, 2020)
The instrumentation of the in vitro culture system has allowed to learn more about the metabolic and growth behavior of Babesia spp. The various applications for in vitro cultivation of Babesia include obtaining attenuated strains for vaccination or pre-munition, the selection of pure lines with different degrees of virulence, cloning, studies on ultrastructure, antigen production for diagnostics, drug sensitivity assessments, and different aspects of parasite biology. Although there are different types of vaccines that have been tested against bovine babesiosis, so far, the only procedure that has offered favorable results in terms of protection and safety has been the use of live attenuated vaccines. In countries, such as Australia, Argentina, Brazil, Uruguay and Israel, this type of vaccine has been produced and used. The alternative to live vaccine other than splenectomized calf-derived biological material, has been the in vitro cultivation of Babesia bovis and Babesia bigemina. The development of in vitro culture of Babesia spp strains in a defined medium have been the basis for the initiation of a source of parasites and exoantigens for a variety of studies on the biochemistry and immunology of babesiosis. Of the above, the use of live immunogens from attenuated strains derived from in vitro culture is highlighted, which has been proposed as an alternative in the control of bovine babesiosis. In several studies performed in Mexico, this type of immunogen applied to susceptible cattle has shown the induction of protection against the experimental heterologous strain challenge with both, Babesia-infected blood and animal exposure to confrontations on tick vector-infested farms. The combination of transfection technologies and the in vitro culture system as integrated methodologies would eventually give rise to the generation of genetically modified live vaccines. However, a greater challenge faced now is the large-scale Babesia parasites cultivation for mass production and vaccine distribution.